THE TYPES OF ABNORMAL BRINING UP MODES OF TEEN-AGE GIRLS WITH UTERINE BLEEDING FROM NONHARMONIC FAMILIES - Zoloto, E.V.; Matytsina, L.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Investigation of the link between psychological stress and hormonal changes, participation of the endocrine system in pathogenesis of pubertal uterine bleedings put forward the study of neurohumoral mechanisms of not only active (stress-reactions) but also passive (anti-stress reactions) which represent a way of adaptation of the organism to the permanently changing surrounding conditions. According to the literature the main danger of our time is the lack of the ability to resist the stress of current life. Important aspect of this problem is the study of hormonal anti-stress mechanisms, which in contrast to stress reactions are investigated insufficiently.